Evaluation of Psychopathological Indices in Students of Zanjan University of Medical Sciences - Sahel Khakpoor borazjani; Arezoo Heshmati Joda; Majid Mohammadi; Zahra Kosari; Saede Zenoozian (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Object: Mental disorders affect various groups, including children, adolescents, and adults, imposing heavy socioeconomic costs on communities. Therefore, the dynamism and efficiency of countries could be guaranteed by improving the mental health level, which leads to enhanced academic levels of students. This study aimed to evaluate the psychopathological indices in students of Zanjan University of Medical Sciences. Materials and Methods: This descriptive study was performed on 400 students of Zanjan University of Medical Sciences during the academic year of 2016-2017. After selecting the subjects by available sampling method, the symptoms checklists 90 revised (SCL-90-R) were provided to students and recollected after completion. Data analysis was performed using descriptive and inferential statistics. Results: In this study, 79% of students were suspected of mental disorders (61.5% mild, 15.3% moderate, and 2.3% severe). Physical complaints and phobic anxiety were significantly higher in female students, compared to male students (P<0.05). Conclusion: According to the results of the study, mental disorders are considerably common among students. Therefore, it is necessary to consider these disorders in the design of prevention and treatment programs.